GENDER QUESTION: DOUBLE DISCRIMINATION OF ZAINICHI IN JAPAN - Н., Ем (Journal of Oriental Studies, 2019)
The gender issue in Asian countries has always been the focus of modern researchers. The place of women in Japanese society defined by patriarchal attitudes based on traditional patriarchy. In this paper, based on an analysis of the literature on Koreans in Japan, the author examines the social status of Korean women in Japan. The difficulties faced by women, related to ethnic discrimination on the part of Japanese society. In addition, features of socioeconomic status of women exacerbated by patriarchal traditions in their own families of Korean women in Japan. On the basis of statistical data on employment of Koreans in the life of society over the last twenty years have identified the main directions of mobility for Korean men. The author suggests that in re sponse to changing historical circumstances, the social status of Korean men has the opportunity to promote social mobility in Japanese society. However, Korean women still remain outside the social mobility. The prospect of changing this situation is still questionable. Key words: Koreans in Japan, status, discrimination, gender, family, employment.